Devising measures to reduce multi-frequency noise load on employees in machining area - Rieznik, Dmytro; Sukach, Serhii; Chencheva, Olga; Lashko, Yevhenii; Kozlovskaya, Tatyana; Volkov, Oleksandr; Petrenko, Ivan; Mukha, Oleh; Hryniuk, Vitaly; Sapa, Serhii (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the process of determining and managing the risks of noise exposure (NE) for employees at the mechanical department when machining metals on a drilling machine (DM). The problem relates to the increase in the risk of an employee receiving an industrial injury because of NE at the workplace of a machine tool. The impact of noise on the human body depends on the duration of exposure, the level of sound pressure, and its intensity. An important characteristic of noise is its frequency composition, as it can affect the perception of sounds and the human body. Prolonged exposure to noise can damage various systems in the human body or cause pain. Therefore, it is important to understand the impact of NE on workers and devise measures to reduce the negative impact on their health and work productivity. The research is based on real-time noise measurements followed by their decomposition into octave frequencies and modeling of noise propagation in the room with and without the use of various types and designs of soundproof barriers (SB). In the course of the study of NE propagation during drilling on the machine, an excess of noise levels at medium and high frequencies near the noise source was found. An employee who works on DM is exposed to high-frequency noise that exceeds the established normative indicators. Therefore, it is necessary to use personal protective equipment for the machine operator and install safety equipment to protect other workplaces. The use of the latter makes it possible to significantly reduce the impact of NE on workers, in particular, at low frequencies by 20.8 %, at medium frequencies by 15.6 %, and at high frequencies by 17.3 %